Runoff erosion in Portugal: a broad overview - Figueiredo, Tomás de (2013)
Soils are generally a scarce natural resource in Portugal as far as productivity is concerned (CNROA, 1983; Agroconsultores e Coba, 1991; Agroconsultores e Geometral, 1995). In fact, the major part of the territory is potentially not suitable for agriculture, corresponding to areas with misuse and over-exploitation of the soil resource in cropland, and to typical marginal land cover by forests and shrubs. The soils with moderate and high suitability are under agricultural use, more or less intensive, that take advantage of their productivity, but that partly experience incorrect management practices (Sequeira et al., 2012, this issue). Besides the crucial support of food and fiber producing activities, soil functions in ecosystems, either cultivated or natural and semi-natural, contribute in providing services and public goods that rise attention to management of large tracts of marginal areas, whilst tackling the problem of persistent population decrease and ageing in rural areas that lead to unmanaged land or abandonment, for instance with consequences for wildfire hazard and control (CIMO, 2009; Rosário, 2011). As so, poorly provided by good soils, enduring threat of several types all over the territory (with a large extent assigned to runoff erosion, CAN, 1980), Portuguese soils require knowledge and protection, to limit resource depletion, recover degraded areas and ensure sustainability pf actual or foreseen land uses and soil-based activities. This opening chapter of the Portuguese case studies presented hereafter aims at providing a general picture of runoff erosion distribution in Portugal, more precisely in the country’s continental territory, adding further information in view calling attention to wider range assessments that rise awareness towards natural resources degradation trends, and sustainable land use and management. A review on the topic of soil erosion in Portugal has been published by Coelho (2006). It is therefore a recent and comprehensive review of relevant research and broad approaches to the identification, quantification and distribution of the problem in Portugal, up to that date. The following text takes Coelho (2006) as a reference information base, that is summarized here and to which is added new information, issued from more recent research and other developments carried out at National level.